Terapi Cognitive Behavior Therapy (CBT) Pada Penderita Obsessive Compulsive Disorder (OCD): Systematic Literature Review - Mohamad Fauzil Adhim Asnawi; Emha Zainul Mukminin (Alpatih Harapan Semesta, 2025)
This article aims to review studies on the application of Cognitive Behavior Therapy (CBT) for individuals with Obsessive Compulsive Disorder (OCD), focusing on the therapeutic approach, target population, and research designs used. The review covers 11 research articles published in international journals between 2014 and 2019. The findings indicate that the majority of study participants were adults, with the main goal of the interventions being to reduce OCD symptoms through CBT. The review confirms the effectiveness of CBT in treating various subtypes of OCD. Furthermore, the findings provide valuable insights for therapists, caregivers, and individuals with OCD in selecting appropriate therapeutic strategies, and serve as a foundation for future research in clinical psychotherapy.